Perencanaan Perbaikan Tata Letak Gudang Penyimpanan Material PT. DSV Solutions Indonesia dengan Metode Class Based Storage - Sajidi Wardana; Mulyadi, Agus; Satriardi, Satriardi; Anggraini, Denny Astrie; Meirizha, St Nova (SURYA TEKNIKA, 2024)
PT. DSV Solutions Indonesia is a logistics company facing challenges in efficient warehouse management. One area, Racking Outbound 1, holds the most Stock Keeping Units (SKU). However, materials are placed haphazardly, ignoring item types, leading to damage and difficulty locating materials, which increases search time. This study aims to improve efficiency by using the Class-Based Storage method to group materials and applying an Activity Relation Chart to plan a new layout based on facility proximity. High-frequency materials are placed in accessible areas, while low-frequency ones are stored farther away. This method reduces average search time by up to 57%, allowing operators to access materials faster, with fewer errors and reduced damage.